11.1: Invited Paper: Brain‐Display Interaction and Its Biomedical Application Using Steady‐State Visual Evoked Potentials. Issue 1 (June 2015) - Lin, Fang‐Cheng; Chien, Yu‐Yi; Zao, John K; Huang, Yi‐Pai; Wang, Yijun; Jung, Tzyy‐Ping; Shieh, Han‐Ping D.
Abstract : Applying steady‐state visual evoked potentials (SSVEPs) on a display system, a novel brain‐display interaction (BDI) system was presented. This study further proposed an imperceptible flickering visual stimulus to make a SSVEP‐based BDI more practical and promising for biomedical applications, such us glaucoma visual field loss diagnosis.